Integrating Domain Governance into Copyright Law: Enhancing Legal Certainty and Regulatory Efficiency in Indonesia - Andini Islamiati Salsabilla; Muhamad Amirulloh; Helitha Novianty Muchtar (Legal Standing : Jurnal Ilmu Hukum, 2026)
The rapid advancement of information and communication technology has transformed the creation, access, and distribution of copyrighted works in the digital environment. However, this development has simultaneously intensified online copyright infringement, particularly through illegal websites operating under registered domain names. This study examines the regulatory role of the Pengelola Nama Domain Internet Indonesia (PANDI) in preventing and combating copyright infringement on the Internet, focusing on domain name governance within the Indonesian legal system. Although PANDI is authorized to administer domain name registration, its involvement in copyright enforcement lacks explicit statutory recognition, resulting in legal uncertainty and normative gaps. Employing a normative juridical method, this research applies Gustav Radbruch’s Theory of Legal Certainty and the Economic Analysis of Law to assess both the doctrinal coherence and the efficiency of existing enforcement mechanisms. The findings indicate that integrating PANDI’s authority into the Copyright Law framework could strengthen legal certainty and establish a more effective and economically efficient preventive system against domain-based digital copyright infringement. This study contributes to the discourse by proposing a model of administrative reinforcement grounded in legal certainty and regulatory efficiency.